2015
DOI: 10.2337/dc15-0811
|View full text |Cite
|
Sign up to set email alerts
|

Randomized, Double-Blind Trial of Triple Therapy With Saxagliptin Add-on to Dapagliflozin Plus Metformin in Patients With Type 2 Diabetes

Abstract: OBJECTIVEThe objective of this study was to assess the efficacy and safety of triple therapy with saxagliptin add-on versus placebo add-on to dapagliflozin plus metformin in adults with type 2 diabetes. RESEARCH DESIGN AND METHODSPatients on stable metformin ( ‡1,500 mg/day) for ‡8 weeks with glycated hemoglobin (HbA 1c ) 8.0-11.5% (64-102 mmol/mol) at screening received open-label dapagliflozin (10 mg/day) plus metformin immediate release (IR) for 16 weeks. Patients with inadequate glycemic control (HbA 1c 7-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 37 publications
12
75
0
Order By: Relevance
“…Pharmacokinetic interactions: [25,33] Clinical trials: [27,28,29,35,36] Article highlights box -Type 2 diabetes (T2D) often requires the combination of several medications with complementary actions to reach glucose control targets while limiting side effects -The combination of a dipeptidyl peptidase-4 inhibitor (DPP-4i) and a sodium-glucose cotransporter type 2 inhibitor (SGLT2i) is an attractive approach for the management of T2D.…”
Section: Pivotal Trial(s)mentioning
confidence: 99%
“…Pharmacokinetic interactions: [25,33] Clinical trials: [27,28,29,35,36] Article highlights box -Type 2 diabetes (T2D) often requires the combination of several medications with complementary actions to reach glucose control targets while limiting side effects -The combination of a dipeptidyl peptidase-4 inhibitor (DPP-4i) and a sodium-glucose cotransporter type 2 inhibitor (SGLT2i) is an attractive approach for the management of T2D.…”
Section: Pivotal Trial(s)mentioning
confidence: 99%
“…The proportion of patients with good glycaemic control (<53mmol/ mol; <7%) was significantly greater, and fasting and postprandial glucose were significantly reduced, with the addition of dapagliflozin (in the trial in which glycaemic control was worse overall) 4 but not when saxagliptin was added. 3 After a further 28 weeks' treatment, the differences in glycaemic control were maintained (see Figure 1). 5,6 The proportion of patients requiring additional treatment if HbA1c exceeded 64mmol/ mol (8%) or who discontinued treatment was lower with saxagliption or dapagliflozin add-on therapy than with placebo (19 vs 28% 5 and 21 vs 48% 6 ).…”
Section: Efficacymentioning
confidence: 93%
“…Adding a DPP-4 inhibitor to metformin/SGLT2 inhibitor was not associated with an increase in the frequency of adverse events in phase 3 trials. 10,13 Urinary tract infection was slightly but consistently more frequently reported with add-on linagliptin (8-10% vs 5-6% with placebo) or add-on saxagliptin (5% vs 4%); hypoglycaemia was rare.…”
Section: Adverse Effectsmentioning
confidence: 98%
“…9 A similar study comparing linagliptin/empagliflozin, empagliflozin, and linagliptin as add-on therapy to metformin found that the linagliptin/empagliflozin combination reduced fasting plasma glucose significantly more than its components; postprandial glucose was not reported. 10 These data should be interpreted cautiously. This use of a DPP-4/SGLT2 inhibitor combination does not match the indication approved for therapeutic use (which would mean that patients were already established on treatment with one of the component drugs and metformin before receiving the combination).…”
Section: Complementary Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation